A pivotal role of bone remodeling in granulocyte colony stimulating factor induced hematopoietic stem/progenitor cells mobilization1. Issue 5 (28th January 2013) - Li, Sidan; Zhai, Qiongli; Zou, Dehui; Meng, Hengxing; Xie, Zhenqing; Li, Changhong; Wang, Yafei; Qi, Junyuan; Cheng, Tao; Qiu, Lugui
Abstract: The majority of hematopoietic stem/progenitor cells (HSPCs) reside in bone marrow (BM) surrounded by a specialized environment, which governs HSPC function. Here we investigated the potential role of bone remodeling cells (osteoblasts and osteoclasts) in homeostasis and stress‐induced HSPC mobilization. Peripheral blood (PB) and BM in steady/mobilized state were collected from healthy donors undergoing allogeneic transplantation and from mice treated with granulocyte colony stimulating factor (G‐CSF), parathyroid hormone (PTH), or receptor activator of nuclear factor kappa‐B ligand (RANKL). The number and the functional markers of osteoblasts and osteoclasts were checked by a series of experiments. Our data showed that the number of CD45 − Ter119 − osteopontin (OPN) + osteoblasts was significantly reduced from 4, 085 ± 135 cells/femur on Day 0 to 1, 032 ± 55 cells/femur on Day 5 in mice ( P  = 0.02) and from 21.38 ± 0.66 on Day 0 to 14.78 ± 0.65 on Day 5 in healthy donors ( P  < 0.01). Decrease of osteoblast number leads to reduced level of HSPC mobilization regulators stromal cell‐derived factor‐1 (SDF‐1), stem cell factor (SCF), and OPN. The osteoclast number at bone surface (OC.N/B.s) was significantly increased from 1.53 ± 0.12 on Day 0 to 4.42 ± 0.46 on Day 5 ( P  < 0.01) in G‐CSF‐treated mice and from 0.88 ± 0.20 on Day 0 to 3.24 ± 0.31 on Day 5 ( P  < 0.01) in human. Serum TRACP‐5b level showed a biphasic trend during G‐CSF treatment. The ratio of osteoblasts number per bone surface (OB.N/B.s) to OC.N/B.s was changed after adding PTH plus RANKL during G‐CSF treatment. In conclusion, short term G‐CSF treatment leads to reduction of osteoblasts and stimulation of osteoclasts, and interrupting bone remodeling balance may contribute to HSPC mobilization. J. Cell. Physiol. © 2012 Wiley Periodicals, Inc.